Writings On The Eight Readings Presentation and Explanation/ المؤلفات في القراءات الثمان عرض وبيان - Alrowithy, Ahmed Humud (Ijaz Arabi Journal of Arabic Learning, 2024)
This research aims at collecting the writings of the Eight Readings without guidance and explanation books, explaining what is present and what is missing, and what is related to that in terms of the emergence of the writing of the Eight Readings and the names of the narrators in those writings. The research followed the descriptive historical approach, arranged the books according to their authors' deaths, and was limited to novel books without guidance and explanation books. The results revealed that the writing of the eight readings coincided with the emergence of the seventh of the seven or shortly after the seven peers of Ibn Mujahid Musba'. The eight readings are the seven with Jacob reading, and the oldest book that has reached us is Al-Badi’s book by Ibn Khalawayh. The research counted eighteen books written in the eight readings; ten are missing. Notably, there is a lack of writing in the eight compared to the seven and the ten, and there are no systems in the eight, in contrast to the number of systems in the seven, ten, three, and others. The researcher recommended searching for missing books of readings in manuscript vaults and investigating.